Lessons learned from SUIT, the Simple User Interface Toolkit - Pausch, Randy; Conway, Matthew; DeLIne, Robert (ACM Transactions on Office Information Systems, 1992)
In recent years, the computer science community has realized the advantages of GUIs (graphical user interfaces). Because high-quality GUIs are difficult to build, support tools such as UIMSs, UI Toolkits and Interface Builders have been developed. Although these tools are powerful, they typically make two assumptions: first, that the programmer has some familiarity with the GUI model, and second, that he is willing to invest several weeks becoming proficient wit the tool. These tools typically operate only on specific platforms, such as DOS, the Macintosh, or UNIX/X-windows. The existing tools are beyond the reach of most undergraduate computer science majors, or professional programmers who wish to quickly build GUIs without investing the time to become specialists in GUI design. For this class of users, the authors developed SUIT, the simple user interface toolkit. SUIT is an attempt to distil the fundamental components of an interface builder and GUI toolkit, and to explain those concepts with the tool itself, all in a short period of time. The authors have measured that college juniors with no previous GUI programming experience can use SUIT productivity after less than three hours. SUIT is a C subroutine library which provides an external control UIMS, an interactive layout editor, and a set of standard 'widgets,' such as sliders, buttons, and check boxes. SUIT-based applications run transparently across the Macintosh, DOS, and UNIX/X platforms. SUIT has been exported to hundreds of external sites on the internet. This paper describes SUIT's architecture, the design decisions made during its development, and the lessons learned from extensive observations of over 120 users.